2020
DOI: 10.1515/jpem-2020-0205
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and long-term follow-up of patients diagnosed with type 1 diabetes mellitus before age 5

Abstract: ObjectivesThis study aimed to determine the effects of continuous subcutaneous insulin infusion (CSII) treatment on anthropometric measurements, mean HbA1c, and insulin dosage in patients diagnosed under 5 years of age and compare with multiple-dose injection therapy (MDI).MethodsChildren with type 1 diabetes mellitus, diagnosed <5 years since 2000 and their 19-year follow-up were evaluated retrospectively. Weight, height, body mass index (BMI), blood pressure, and HbA1c values were recorded for each visit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Sources: [16,[23][24][25][26][27][28][29][30][31][32][33] Risk of bias in each article. Eleven articles were assessed: one showed a high risk of bias, six showed some concerns, and the remaining four showed a low risk of bias.…”
Section: Figure 2: Risk Of Bias Of Randomized Control Trials With Ris...mentioning
confidence: 99%
“…Sources: [16,[23][24][25][26][27][28][29][30][31][32][33] Risk of bias in each article. Eleven articles were assessed: one showed a high risk of bias, six showed some concerns, and the remaining four showed a low risk of bias.…”
Section: Figure 2: Risk Of Bias Of Randomized Control Trials With Ris...mentioning
confidence: 99%
“…Although it has been clearly shown that T1D causes growth and developmental retardation in the years of crystallized insulin use, it is predicted that the negative effect of the disease on the growth and development of children will decrease with the introduction of analog insulins, pump treatments, and sensors. [1][2][3][4] Children with growth retardation usually have poor glycemic control and are diagnosed early and with long-term follow-up. [5,6] In our study, it was aimed to scan the prevalence of malnutrition in children with T1D, which is considered a chronic disease, with the mid-upper arm circumference (MUAC) measurement and to compare the Z-score results used in evaluating this measurement with the body mass index-standard deviation score (BMI-SDS) of Turkish children.…”
Section: Introductionmentioning
confidence: 99%